Evaluation of Relevant CD Markers in Basal Cell Carcinoma Patients in Diyala Province, the Republic of Iraq - Kadhim, Hala Yaseen; Abbas, Ali Hafedh; Ibrahim, Thekra Atta (Iraqi Journal of Science, 2025)
Basal Cell Carcinoma (BCC) is the most highly prevalent type of skin cancer in the world, where BCC incidence has increased significantly in the last few years. There were many components of the immune system that were reported to play a remarkable role in BCC appearance and development. Among them, three specific clusters of differentiation (CD) biomarkers (CD25, CD68 and CD10, also termed as MME) were studied as prognostic markers with increased levels in the sera of immune-related cancers. The current investigation aimed to evaluate the levels of these biomarkers in the sera of 33 patients who have BCC compared with 55 healthy individuals (control). The results demonstrated significantly increased levels of CD25, CD68 and CD10/MME in the BCC group compared to the controls, suggesting a potential role as biomarkers, in addition to their correlation with BCC aggressiveness. The present investigation could be the first in Iraq that tried to evaluate the levels of these CDs in BCC patients. The present investigation suggests potential implications of these CDs for the development of immunotherapeutic strategies and as prognostic markers for BCC, along with their possibility of predicting the risk of new BCC tumors.